2023
DOI: 10.1039/d3fb00003f
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable plant protein: an up-to-date overview of sources, extraction techniques and utilization

Abstract: Protein is a vital macronutrient that helps in survival of human beings. Its major function includes body building, promoting normal growth and maintenance. The two key sources of protein in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 107 publications
0
6
0
Order By: Relevance
“…However, the huge rise in the temperature leads to the extraction of other undesirable impurities, which require additional processing for purification. While we discuss a few examples, alkaline extraction is an inexpensive chemical extraction method in which protein dissolution occurs in an alkaline medium, with the disadvantage of protein denaturation under highly alkaline conditions during the extraction procedure [115]. Also, the increase in temperature and extraction time induces thermal precipitation and denaturation effects that may degrade the quality of proteins [115].…”
Section: Protein Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the huge rise in the temperature leads to the extraction of other undesirable impurities, which require additional processing for purification. While we discuss a few examples, alkaline extraction is an inexpensive chemical extraction method in which protein dissolution occurs in an alkaline medium, with the disadvantage of protein denaturation under highly alkaline conditions during the extraction procedure [115]. Also, the increase in temperature and extraction time induces thermal precipitation and denaturation effects that may degrade the quality of proteins [115].…”
Section: Protein Extraction Methodsmentioning
confidence: 99%
“…While we discuss a few examples, alkaline extraction is an inexpensive chemical extraction method in which protein dissolution occurs in an alkaline medium, with the disadvantage of protein denaturation under highly alkaline conditions during the extraction procedure [115]. Also, the increase in temperature and extraction time induces thermal precipitation and denaturation effects that may degrade the quality of proteins [115]. Enzyme-assisted extraction is a biochemical method that relies on the use of enzymatic breaking of the rigid cell wall to boost the protein yield.…”
Section: Protein Extraction Methodsmentioning
confidence: 99%
“…After freeze-drying, the crude protein obtained from the chia seeds in this study was almost 70.8%, which was higher than that reported by Xue-li et al (2018)[46], who reported a yield of 61.52%. Generally, the protein extraction yield from chia seeds is comparatively higher than that from cottonseeds, sesame, peanuts, and soybeans due to abundant high-swelling mucilage gel formation with water, which hinders the ability of the protein to interact with the alkali solution [47]. Enzymatic hydrolysis by pectinase is useful for increasing the extraction rate of crude protein by lowering the degradation of galacturonic acid in chia seed mucilage saccharides.…”
Section: Isolation Of Chia Seeds Protein Hydrolysate By Crude Proteas...mentioning
confidence: 99%
“…With advances in plant protein extraction, pea proteins are also considered complete proteins because they contain all nine essential amino acids [174,175]. Plant proteins have poorer proteolytic digestibility and, thus, lower protein qualities because of the presence of fiber and other antinutrition components, like trypsin inhibitors [176]. Most antinutritive factors are primarily found in the cotyledon and hull fractions of legume seeds, while processing techniques can be applied to decrease the antinutritive-factor levels [177].…”
Section: Plant Proteinsmentioning
confidence: 99%
“…However, deliberate process-induced modifications can be conducted to improve the protein functionality, including enzymatic modification, extrusion, high-pressure processing, high-power ultrasound treatment, etc. [176,179,[183][184][185]. Extrusion, particularly, can align the protein fibers and create a meat-like structure [185].…”
Section: Plant Proteinsmentioning
confidence: 99%